An Assessment of the impact of government input subsidies on household food production. a case of maize production in Zaka district - Masimba, James (BUSE, 2021)
Thei government Input iSubsidy Programme in Zimbabwe hasi receivedi national recognition fori improvingi the inational foodi securityi but however limitedi informationi is availablei on theieffectiof thisi programmei on ,householdi food, production. There is need for a better understanding particularly to the outcomes of these kind of programmes since their impacti on foodi production ati householdi level remains vaguei. Thisi studyi employedi descriptive statistics to determine farmers opinion on the interrelationships that exist between variables that either determine access to input subsidy or increase production among the 100 randomlyi chosen householdsi, (52 beneficiaries and 48 non-beneficiaries). The studyi alsoi evaluatedifactors affecting accessi to input subsidies. Resultsifrom thei Probit regressioni model showedi that only 3 variables were significant thus only land size, household size and education can be used to explain access to inputs subsidies. Variables like age, income and gender were not statistically significant therefor have limited influence in explaining access to input subsidies in Zaka district. The study also assessed the contribution of agricultural input subsidies on household food production. Results of the multiple regression model indicated that only 2 variables were significant therefor only access to credit and land size can be used to explain changes in crop yield in Zaka district. Variables like education, age, income were not statistically significant therefor has limited influence in explaining changes in crop yield in Zaka district. Howeveri, thei severityi of householdi food insecurityi is ia causei for concerni as a greater percentage of the population was noted to be food insecure due to low yields.The impact therfor for the input incentive initiative is not the same at national level and at household level given the highi percentage of foodi insecurei householdsi notedi fromi this studyi. Hencei, studyi aims to study impact of this programme on household food production to see if the input support program oni itsi owni guarantee increased yields or not or guarantee food security at a household level or not.
Keywords: Government input subsidies; Maize production; Household food production